Evaluation of electroluminescence of AlGaN/GaN HEMT on free-standing GaN substrate. (1st September 2022) - Ma, Qiang; Ando, Yuji; Tanaka, Atsushi; Wakejima, Akio
Abstract: This paper investigated electroluminescence (EL) in AlGaN/GaN high electric mobility transistors fabricated on a free-standing GaN substrate (GaN-on-GaN) with ones on a SiC substrate (GaN-on-SiC) as a reference. When a drain voltage ( V ds ) of the GaN-on-GaN was increased, the EL peak was kept beside the gate, indicating that the highest electric field region stayed in the vicinity of the gate. On the other hand, EL of the GaN-on-SiC shifted from the gate to the drain electrode under an increased V ds . Our results indicate that the high-electric-field tolerance of GaN-on-GaN is higher than that of GaN-on-SiC, indicating that GaN-on-GaN is more suitable for high-voltage operation.